2022
DOI: 10.1186/s12871-022-01742-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ultrasound-guided lung recruitment maneuvers on atelectasis in lung-healthy patients undergoing laparoscopic gynecologic surgery: a randomized controlled trial

Abstract: Background Atelectasis is the primary cause of hypoxemia during general anesthesia. This study aimed to evaluate the impact of the combination of recruitment maneuvers (RM) and positive end-expiratory pressure (PEEP) on the incidence of atelectasis in adult women undergoing gynecologic laparoscopic surgery using pulmonary ultrasound. Methods In this study, 42 patients with healthy lungs undergoing laparoscopic gynecologic surgery were randomly divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Whether the control group uses LRM is also worth further discussion. Although the control group in some studies using low tidal volume and PEEP, they did not undergo lung re-expansion during operation [6, 22,23,24,25,26,27], while the control group in the remaining studies used non-ultrasound-guided RM during operation [14,15]. Whether or not the control group had experienced postoperative atelectasis, the data demonstrated that the incidence of the condition was decreased in the ultrasound-guided group.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Whether the control group uses LRM is also worth further discussion. Although the control group in some studies using low tidal volume and PEEP, they did not undergo lung re-expansion during operation [6, 22,23,24,25,26,27], while the control group in the remaining studies used non-ultrasound-guided RM during operation [14,15]. Whether or not the control group had experienced postoperative atelectasis, the data demonstrated that the incidence of the condition was decreased in the ultrasound-guided group.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of postoperative atelectasis in adults and children were reported in the nine studies with 443 patients[6, 14,15,22,23,24,25,26,27]. The results showed that ultrasound-guided LRM reduced the incidence of postoperative atelectasis in adults (RR = 0.49; 95% CI: 0.36 to 0.67; p < 0.05; heterogeneity p > 0.10; I 2 = 0%)(Fig.…”
Section: Subgroup Analysis Of the Effect Of Adults And Children On Po...mentioning
confidence: 96%
See 3 more Smart Citations